Denitrification, anammox, and dissimilatory nitrate reduction to ammonium across a mosaic of estuarine benthic habitats - Jian‐Jhih Chen; Dirk V. Erler; Naomi S. Wells; Jianyin Huang; David T. Welsh; Bradley D. Eyre (Limnology and Oceanography, 2021)
Estuaries play a key role in moderating the flow of nitrogen (N) to marine ecosystems. However, the magnitude of this N removal can vary dramatically both within and between estuaries due to the benthic habitats present. Here, we compare denitrification, coupled nitrification–denitrification, anammox, and dissimilatory nitrate reduction to ammonium (DNRA) across a mosaic of benthic habitats in the subtropical Noosa River Estuary, Australia. Using 15 N tracer techniques and passive pore‐water samplers, we show that coupled nitrification–denitrification was the dominant pathway for N 2 production across all habitats, with higher rates in vegetated habitats (10–70 μ mol N m −2 h −1 ) compared to bare sediments (0.9–2 μ mol N m −2 h −1 ). Unusual pore‐water profiles in the macroalgal sediments suggest the presence of sulfur‐driven anoxic nitrification of NH 4 + to NO 3 − and N 2 . A benthic N budget showed that combined denitrification and coupled nitrification–denitrification accounted approximately 96% of the N 2 production, while DNRA accounted for 9% of total NO 3 − reduction pathways in the Noosa River Estuary. The macroalgae habitat contributed 76% of total N removal via N 2 production and 65% of N retention via DNRA, despite accounting for only 25% of the total surface area. We show a strong relationship between seagrass and macroalgae area and N 2 production ( r 2 = 0.8; p